Development of pattern recognition based on nanosheet–DNA probes and an extendable DNA library. Issue 15 (9th July 2021) - Qi, Jiawei; Rao, Pinhua; Wang, Lele; Xu, Li; Wen, Yanli; Liang, Wen; Yang, Zhenzhou; Yang, Xue; Zhu, Changfeng; Liu, Gang
Abstract : We designed a pattern recognition based on nanosheet materials and a DNA library based on binary coding. Abstract : Pattern recognition, also called "array sensing, " is a recognition strategy with a wide and expandable analysis range, based on high-throughput analysis data. In this work, we constructed a sensor array for the identification of targets including bacterial pathogens and proteins by using FAM-labeled DNA probes and 2D nanosheet materials. We designed an ordered and extendible DNA library for the collection of recognition probes. Unlike traditional DNA probes with random and massive sequences, our DNA library was constructed following a 5-digit binary number (00000–11111, 0 = CCC, and 1 = TTT), and especially, 8 special symmetry sequences were chosen from the library. Two different nanosheet materials were used as the quencher. When targets were added, the interaction between DNA and the nanosheets was competitively affected, and as a result, the fluorescence signal changed accordingly. Finally, by using our fluorescent sensor array, 17 bacteria and 8 proteins were precisely recognized. We believe that our work has provided a simple and valuable strategy for the improvement of the recognition range and discrimination precision for the development of pattern recognition.